REALIZATION OF ASYNDETON AND POLYSYNDETON IN THE LONGUS’S NOVEL “DAPHNIS AND CHLOE” - Chakal (Makar), Inesa (Casa Editorială Demiurg, 2015)
In the article the functions of the figures of asyndenton and polysyndeton as syntactic means of the text organization of “Daphnis and Chloe” (an ancient Greek novel of the end of the second century AD written by Longus) were clarified. It was found out, that these figures are important components of the writer’s idiostyle, his world outlook.
Keywords: asyndenton; polysyndeton; expressiveness; idiostyle; Longus